Facet‐Dependent Cold Welding of Au Nanorods Revealed by Liquid Cell Transmission Electron Microscopy - Wen Wang; Dongxing Song; Fangjie Meng; Sufeng Fan; Ran Cai; Shaobo Cheng; Chongxin Shan; Tao Xu; Haimei Zheng; Litao Sun (Advanced Science)
Abstract Cold welding of metals at the nanoscale has been demonstrated to play a significant role in bottom‐up manufacturing and self‐healing processes of nanostructures and nanodevices. However, the welding mechanism at the nanoscale is not well understood. In this study, a comprehensive demonstration of the cold welding process of gold nanorods with different modes is presented through in situ liquid cell transmission electron microscopy. The experimental results and molecular dynamics simulations reveal that the nanorods are welded through the facet‐dependent atomic surface diffusion and rearrangement along {100} facets. The density functional theory calculations indicate that the preferred coalescence of two {100} surfaces is thermodynamically favorable. Unlike the prevalent “oriented attachment” in the nanoparticle coalescence, the misalignment of nanorod orientations and local stresses can induce grain boundaries and stacking faults in the welded interface.